ANALISIS TERHADAP PUTUSAN TINDAK PIDANA PEMBUNUHAN BERENCANA OLEH OKNUM TNI ( STUDI KOMPARATIF PUTUSAN NOMOR: 78-K/PM I-04/AD/VII/2019 DAN NOMOR : PUT/217-K/PM.II- 09/AD/XI/2009 - fitriyani, fitriyani; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The planned murder crime committed by TNI personnel Prada Deri againsthis lover in decision Number: 78-K / PM I-04 / AD / VII / 2019 and KopdaKhairul Anwar against his wife in decision Number: PUT / 217-K / PM.II -09 /AD / XI / 2009) was subject to punishment in Article 340 of the Criminal Code.The purpose of writing this thesis is to analyze the Decision of the Crime of Planned Murder byMilitary Personnel (Comparative Study of Decisions Number: 78-K / PM I-04 / AD / VII / 2019and Number: PUT / 217-K / PM.II-09 / AD / XI / 2009) and explains the judge's consideration inimposing a sentence on a defendant who committed premeditated murder.The approach method that I use is a normative juridical approach. This type ofresearch used by the author in this study is to use descriptive research. The method ofdata collection in this study uses literature study techniques.From the results of researchand discussion, the legal regulations regarding the crime of murder committed bymembers of the TNI are regulated in the provisions of the Criminal Code (KUHP) and theMilitary Criminal Code (KUHPM). Law enforcement against the Defendant Deri in themurder case of his lover in the decision Number: 78-K / PM I-04 / AD / VII / 2019 issubject to the main criminal, in the form of life imprisonment, is also subject to additionalpunishment, namely in the form of dismissal from military service. And according to theauthor's analysis, the verdict is not correct because in the case it is more appropriate tosubject ordinary murder, not premeditated murder. Meanwhile, law enforcement againstthe Defendant Khoirul Anwar in the murder case against the verdict Number: PUT / 217-K / PM.II-09 / AD / XI / 2009) is subject to the main crime, in the form of imprisonment of13 (thirteen) years, is also subject to additional punishment, namely in the form ofdismissal from military service. According to the author's analysis, the decision wascorrect because it had fulfilled the plan beforehand.The judge's consideration in imposing the sentence against the Defendant Deri inthe murder case of his lover in decision Number: 78-K / PM I-04 / AD / VII / 2019 and inthe case of the Defendant Khoirul Anwar in the case of murdering his wife in the decisionNumber: PUT / 217- K / PM.II-09 / AD / XI / 2009) are juridical considerations such asfacts revealed in the trial such as the jpu indictment, witness statements, evidence andnon-juridical considerations such as the background of the perpetrator, the defendant'sactions, the conditions at the time incident.Keywords:lore-premeditatet mulder- military court